Plant Species Composition and the Carrying Capacity of Grazing Fields in Taman Jaya West Java - H. Simbolon; S. Prawiroatmodjo; S. N. Prijono (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1986)
-